Correction of Sharia Value Added Concept: Considering Theoretical Basic Concepts of Accounting Financial Reports - Wasih Latuh Rahmi; Yenni Samri Juliati Nasution (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Sharia value added involves high ethical principles in business, such as not being involved in usury (interest), gambling, or other illicit activities. This can provide trust and satisfaction to consumers who value the moral aspects of business transactions. This study aims to find out how Sharia accounting principles underlie sharia added value, the distribution of welfare for limited groups, and efforts to improve and correct the concept of sharia added value. This study uses a qualitative research method that describes data using a series of sentences. The method used in this research is the descriptive method. The descriptive method is a method whose data sources are words, pictures, and data from books, journals, and other scientific works. The results of this study are that there are several principles of Sharia accounting that underlie Sharia value added including the principle of justice (adl), the principle of justice, the principle of responsibility, then the principle of transparency, and the principle of togetherness, and the principle of prohibition of usury (qardh). Efforts to improve the correction of the concept of Sharia value-added can be done by clarifying the weaknesses and challenges that exist in the concept of Sharia value-added, perfecting performance indicators by evaluating and improving the performance indicators used in measuring Sharia value-added, training, and industry collaboration with Islamic financial institutions, companies, and supervisory institutions to develop better standards, guidelines, or frameworks.